Retour sur le drame de l’Île des Diamants : l’investissement immobilier des grands projets urbains à Phnom-Penh - Gabriel Fauveaud (EchoGéo)
Through this article, we would like to underline few main dynamics of the contemporary urban development of Phnom‑Penh after more than 350 people died on Diamonds Island, a new private large scale project under construction. The Diamonds Island project questions the role of the large scale real-estate investors in the fabrication of the urban space. We will get onto the evolution of the internationalization of the production of the urban space. By this end, we will be able to replace the “urban project” within the institutional and historical local reality. Through the particular example of the Diamonds Island, we will approach the evolution of the urban modernity understood as a marketing strategy. Finally, the Diamond Island tragedy reveals the antagonisms of the current urban politic and interrogates the capacity of the private investors to construct a sustainable city.